The island : a novel - Hilderbrand, Elin (New York : Reagan Arthur/Back Bay Books, 2011)
After her daughter Chess' ex-fiancé dies in a rock-climbing accident, Birdie Cousins encourages her younger daughter, Tate, and her sister, India, to join her and Chess on Tuckernuck Island for a month, a time when deep secrets are soon revealed.
Keywords: Women -- Massachusetts -- Nantucket -- Fiction; Domestic fiction